2018
DOI: 10.5213/inj.1836226.113
|View full text |Cite
|
Sign up to set email alerts
|

Treadmill Exercise Improves Motor Function by Suppressing Purkinje Cell Loss in Parkinson Disease Rats

Abstract: PurposeRotenone is the most widely used neurotoxin for the making Parkinson disease (PD) animal model. The neurodegenerative disorder PD shows symptoms, such as slowness of movements, tremor at resting, rigidity, disturbance of gait, and instability of posture. We investigated whether treadmill running improves motor ability using rotenone-caused PD rats. The effect of treadmill running on PD was also assessed in relation with apoptosis of cerebellar Purkinje cells. MethodsTreadmill running was applied to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 27 publications
3
31
0
Order By: Relevance
“…They reported that rotenone injection shortened the latency time; meanwhile, treadmill running lengthened the latency to fall of the rotenone-treated. Shin et al, reported decrease in depressive-like behaviors in exercised rotenone treated rats (27,29). In accordance with our study, Chen et al (30) reported signi cant improvement of Rota rod test in treadmill exercised 6-OHDA group , and signi cant gait improvement with signi cant improvement in overlap, stride length and base width with treadmill exercise.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…They reported that rotenone injection shortened the latency time; meanwhile, treadmill running lengthened the latency to fall of the rotenone-treated. Shin et al, reported decrease in depressive-like behaviors in exercised rotenone treated rats (27,29). In accordance with our study, Chen et al (30) reported signi cant improvement of Rota rod test in treadmill exercised 6-OHDA group , and signi cant gait improvement with signi cant improvement in overlap, stride length and base width with treadmill exercise.…”
Section: Discussionsupporting
confidence: 90%
“…Recently many authors studied the effects of treadmill and other means of exercise on rat models of PD. Lee et al, and Shin et al (27,29), both studied the effects of treadmill exercise on rotenone-treated rats. They reported that rotenone injection shortened the latency time; meanwhile, treadmill running lengthened the latency to fall of the rotenone-treated.…”
Section: Discussionmentioning
confidence: 99%
“…Treadmill exercise has been approved to ameliorate motor disturbance in Parkinson's disease through inhibition of dopaminergic neuron loss and cerebellar Purkinje neuron apoptosis as well as reduce of neurodegeneration in Alzheimer's disease (AD) . However, therapeutic treadmill exercise has been regarded as heterogeneous issue due to the diversified treadmill protocols and different physical situation.…”
Section: Introductionmentioning
confidence: 99%
“…The previously mentioned somatic storage reflex, also known as the pelvic-to-pudendal or guarding reflex, can occur in situations such as laughing, sneezing, and coughing that induce a rise in vesical pressure due to increased abdominal pressure or detrusor pressure. L-glutamate, which is the primary excitatory transmitter in the reflex arc, triggers action potentials by stimulating N-methyl-D-aspartate, α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid, and transmembrane ionotropic receptors, and these action potentials stimulate the secretion of acetylcholine, thereby causing contraction of rhabdosphincter muscle fibers (Lee et al, 2018). The urinary incontinence occurs because of this stress if this guarding reflex does not function properly.…”
Section: Innervation Of the Lower Urinary Tractmentioning
confidence: 99%
“…The axons of LMUs pass through the efferent anterior or ventral roots, where motor nerves and autonomic nerves run when they exit the spinal cord. At that point, LMUs extend to the neuromuscular plate or neuromuscular junction, where they are responsible for innervation at muscles that are under voluntary control (Lee et al, 2018). Onuf's nucleus is a defined group of neurons that maintain continence of micturition and defecation and induce muscle contraction during orgasm.…”
Section: Introductionmentioning
confidence: 99%